2022
DOI: 10.3389/fped.2022.910497
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal ultrasound phenotypic and genetic etiology of the 17q12 microduplication syndrome

Abstract: BackgroundSeveral studies have reported on the clinical phenotype of the 17q12 microduplication syndrome, a rare autosomal dominant genetic disorder, in children and adults, but few have reported on its prenatal diagnosis. This study analyzed the prenatal ultrasound phenotypes of the 17q12 microduplication syndrome to improve the understanding, diagnosis, and monitoring of this disease in fetuses.MethodsA retrospective analysis of 8,200 pregnant women who had received an invasive antenatal diagnosis at tertiar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…CNVs have been detected in pregnant women with fetal USMs, suggesting that more attention should be paid to CNVs in pregnant women with fetal USMs, especially P CNVs [8, 13,[23][24][25][26]. In our study cohort, CNVs were more common than aneuploidies.…”
Section: Discussionmentioning
confidence: 80%
“…CNVs have been detected in pregnant women with fetal USMs, suggesting that more attention should be paid to CNVs in pregnant women with fetal USMs, especially P CNVs [8, 13,[23][24][25][26]. In our study cohort, CNVs were more common than aneuploidies.…”
Section: Discussionmentioning
confidence: 80%
“…The main clinical features of 17q12 microdeletion syndrome are structural or functional abnormalities in the kidney and urethra, type 5 diabetes, and neurodevelopmental or neuropsychiatric disorders. [15] It has been reported that 11 cases of 17q12 microdeletion fetus have enhanced renal echo ultrasound, 2 cases also accompanied by kidney enlargement, [4] 88% of 17q12 microdeletion fetal prenatal ultrasound enhanced renal echo, but no obvious change in kidney size. [7] In our study, 12 cases showed enhanced renal echo among 14 patients with 17q12 microdeletion syndrome, which was consistent with the above report.…”
Section: Discussionmentioning
confidence: 99%
“…The main clinical features of 17q12 microdeletion syndrome are structural or functional abnormalities in the kidney and urethra, type 5 diabetes, and neurodevelopmental or neuropsychiatric disorders. [15] It has been reported that 11 cases of 17q12 microdeletion fetuses have exhibited enhanced renal echo ultrasound, and 2 cases were accompanied with kidney enlargement. [4] In another study, a total of 88% of 17q12 microdeletion fetuses presented with enhanced prenatal ultrasound renal echo, but no obvious changes in kidney size.…”
Section: Discussionmentioning
confidence: 99%